THU0255 A new bone prognostic factor in multiple myeloma (mm): level serum cross-laps (ctx) at diagnosis. (1st June 2001) - Duché, A; Leleu, X; Duhamel, A; Delannoy, V; Facon, T; Brazier, M
Abstract : Background: In MM b2 microglobuline (b2) and chromosome 13 deletion (Ch 13) have demonstrated an adverse prognostic impact on response, duration and survival. Bone turn-over marquers are studied in management and follow-up of MM. Objectives: The aim of this study was to demonstrate that a new bone resorption marquer, ie. initial serum CTX level at diagnosis, is a potential prognostic factor in MM. Methods: Between March 1990 and june 2000, 122 MM patients were hospitalised in our department. They all have an evaluation of demographic, usual biologic parameters, and an extensive evaluation of prognostics parameters at diagnosis, including b2, Ch 13 and CTX. Serum level CTX were assessed by ELISA test. Event free survival, relapse and death were achieved during follow-up. Descriptive analysis was performed, and correlations were obtained by univariate analysis. Results: descriptive analysis showed: mean age 61 years; men 57%, ; b2 > 3 mg/l, 45%; Ch 13, 32, 5%; C Reacive Proteine > 6 mg/l, 35%; stage accordind to Durie -Salmon (I, II, III) respectively 17.6, 25, 57.4%; IgG, IgA, other Ig respectively 62, 25, 13%; number of bone lesions > 6, 21%, relapse 59%, death 42%. ROC curved didn't permitted to determined ideal threshold for CTX. Median CTX level (CTX = 2470 pmol/l) at diagnosis was correlated to survival and relapse and CTX level at diagnosis (dCTX) was correlated to all prognostics parameters studied in an univariate stastistical analysis. DCTX > 2470 pmol/l is correlated to poor survival (p = 0.0151) with event free survival at 30 months descriptive analysis showed: mean age 61 years; men 57%, ; b2 > 3 mg/l, 45%; Ch 13, 32, 5%; C Reacive Proteine > 6 mg/l, 35%; stage accordind to Durie -Salmon (I, II, III) respectively 17.6, 25, 57.4%; IgG, IgA, other Ig respectively 62, 25, 13%; number of bone lesions > 6, 21%, relapse 59%, death 42%. ROC curved didn't permitted to determined ideal threshold for CTX. Median CTX level (CTX = 2470 pmol/l) at diagnosis was correlated to survival and relapse and CTX level at diagnosis (dCTX) was correlated to all prognostics parameters studied in an univariate stastistical analysis. DCTX > 2470 pmol/l is correlated to poor survival (p = 0.0151) with event free survival at 30 months (versus 60 months). DCTX is statistically significatively associated to sexe (p = 0.0383), b2 > 3 mg/l (p = 0.0007), Ch 13 (p = 0.0504), C Reactive Proteine > 6 mg/l (p = 0.0348), stage according to Durie -Salmon (p = 0.0015), number of bone lesions (p = 0.0330), poor survival (p = 0.089), and relapse (p = 0. 0018). Conclusion: We demonstrate in this retrospective study that dCTX level appears as a new prognostic factor on survival and relapse. It is associated to other prognostics factors, stage according to Durie -Salmon, and high number of bone lesions. Multivariate analysis must be performed to confirm the powerful of the combination of b2, Ch 13 and dCTX, as prognostic tool to sceen patients and manage thepareutics decisions.